Dual functional states of R406W-desmin assembly complexes cause cardiomyopathy with severe intercalated disc derangement in humans and in knock-in mice - Herrmann, Harald; Cabet, Eva; Chevalier, Nicolas R.; Moosmann, Julia; Schultheis, Dorothea; Haas, Jan; Schowalter, Mirjam; Berwanger, Carolin; Weyerer, Veronika; Agaimy, Abbas; Meder, Benjamin; Müller, Oliver J.; et al. (Circulation, 2020)
Background:Mutations in the human desmin gene cause myopathies and cardiomyopathies. This study aimed to elucidate molecular mechanisms initiated by the heterozygous R406W-desmin mutation in the development of a severe and early-onset cardiac phenotype.Methods:We report an adolescent patient who underwent cardiac transplantation as a result of restrictive cardiomyopathy caused by a heterozygous R406W-desmin mutation. Sections of the explanted heart were analyzed with antibodies specific to 406W-desmin and to intercalated disc proteins. Effects of the R406W mutation on the molecular properties of desmin were addressed by cell transfection and in vitro assembly experiments. To prove the genuine deleterious effect of the mutation on heart tissue, we further generated and analyzed R405W-desmin knock-in mice harboring the orthologous form of the human R406W-desmin.Results:Microscopic analysis of the explanted heart revealed desmin aggregates and the absence of desmin filaments at intercalated discs. Structural changes within intercalated discs were revealed by the abnormal organization of desmoplakin, plectin, N-cadherin, and connexin-43. Next-generation sequencing confirmed the DES variant c.1216C>T (p.R406W) as the sole disease-causing mutation. Cell transfection studies disclosed a dual behavior of R406W-desmin with both its integration into the endogenous intermediate filament system and segregation into protein aggregates. In vitro, R406W-desmin formed unusually thick filaments that organized into complex filament aggregates and fibrillar sheets. In contrast, assembly of equimolar mixtures of mutant and wild-type desmin generated chimeric filaments of seemingly normal morphology but with occasional prominent irregularities. Heterozygous and homozygous R405W-desmin knock-in mice develop both a myopathy and a cardiomyopathy. In particular, the main histopathologic results from the patient are recapitulated in the hearts from R405W-desmin knock-in mice of both genotypes. Moreover, whereas heterozygous knock-in mice have a normal life span, homozygous animals die at 3 months of age because of a smooth muscle-related gastrointestinal phenotype.Conclusions:We demonstrate that R406W-desmin provokes its severe cardiotoxic potential by a novel pathomechanism, where the concurrent dual functional states of mutant desmin assembly complexes underlie the uncoupling of desmin filaments from intercalated discs and their structural disorganization.
Gesehen am 05.02.2021